Analisis Komparatif Model Indeks Tunggal dan Model Random Dalam Penentuan Portofolio Optimal: - Riang Adene Rada (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The purpose of this study is to analyze the determination of the portfolio with the Single Index Model which can provide optimal returns compared to determining the portfolio using the Random Model on the Kompas 100 Index stock on the Indonesia Stock Exchange for the period 2017 - December 2021 or vice versa. The population of this research is all issuers of shares that are incorporated into the Indeks Kompas 100 for the period 2017 – December 2021 with a selected sample of 30 companies. The research method used in this study is the paired sample t-test difference test. The results of the research and statistical tests show that the Single Index Model provides a more optimal return than using the Random Model.